Fundamental even leaky mode in microstrip line loaded with shorting vias. Issue 1 (1st January 2017) - Liu, Juhua; Li, Yuanxin; Long, Yunliang
Abstract : An even leaky mode in a microstrip line loaded with periodic shorting vias at the centre is investigated. The even leaky mode has a lower cutoff frequency than that of the first higher mode (odd mode). Thus, it is a fundamental leaky mode. The even leaky mode can generate dual symmetrical side beams that scan with frequency, similar to the second higher mode (even mode) in a non‐loaded microstrip line. The dispersion characteristic of the even leaky mode is analysed efficiently with the method of auxiliary sources and validated with HFSS. Based on the leaky even mode, two leaky‐wave antennas with different feeding structures are designed. Measured results for the two antennas are consistent with simulated and theoretical results.